Organized Women's Responses to Urban Poor Housing: Towards Transformations in Housing in the Philippines - Laguilles-Timog, Rowena A. (Review of Women's Studies; Vol 28 (2018): Review of Women's Studies Volume XXVIII (2018), 2023)
This study examines the Philippine housing policy context, the housing situations and institutional contexts of women living in the urban poor, and organized women's housing perspectives on and action towards adequate housing. By looking at the housing problem from a feminist standpoint and by using the Social Relations Framework, the study intends not only to critique but also to propose an alternative approach to housing in the Philippines. Among the findings of the study are: 1) the Philippine housing system, despite efforts at becoming more gendered, continues to neglect to recognize and respond to gender issues in housing, especially because of its market orientation; 2) social institutions, as the site for women's material conditions and social positions, cause women greater burden as they struggle to improve their housing situation; and 3) women's vantage point affords them a guiding perspective on housing that places people's lives at its center. Among the study's recommendation for policymakers is the feminist transformation of the housing system that not only supports women organizing through mechanisms that challenges the institutionalization of gender roles and relations, but that also shifts away from its market orientation and works towards human well-being.